Clinical Decision Support System: A Pragmatic Tool to Improve Acute Exacerbation of COPD Discharge Recommendations. (2nd January 2019) - Epstein, Danny; Barak-Corren, Yuval; Isenberg, Yoni; Berger, Gidon
Abstract: Acute exacerbations of chronic obstructive pulmonary disease (COPD) are associated with significant mortality, morbidity and increased risk for further exacerbations. Therefore, appropriate measures for prevention of further exacerbations should be initiated before discharge. Unfortunately, this opportunity for treatment review and change in disease course is often missed. We designed a decision support tool to automatically generate discharge recommendations for COPD patients based on the Global Initiative for Chronic Obstructive Lung Disease (GOLD) report. A pre- and post-intervention study was conducted including data from 24 months before and 18 months after the implementation of the tool. The rate of adherence of the discharge recommendations to the report was measured. Overall, 536 patients were included in the pre-intervention cohort and 367 in the intervention cohort. Demographic and clinical features were similar between the two groups. After introduction of the tool, the percentage of patients discharged with long-acting medications increased from 42% to 84%, recommendations for smoking cessation increased from 32% to 91%, for vaccination from 13% to 92%, and for follow-up visit in a pulmonology clinic from 72% to 98%. Of the patients given prescriptions for long-acting bronchodilators, 54% purchased these after discharge versus 20% of the patients without such prescriptions. Decision-support tools can significantly improve adherence to guidelines among patients discharged after hospitalization due to Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) and potentially improve their clinical course.